Penerapan Sistem Informasi Akuntansi Penjualan Dalam Menunjang Efektifitas Pengendalian Intern Penjualan - Setiawan, Hendra; Munawar, Aang; Laura, Sorta (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
The purpose of this research is to analyse the application of accounting information system sales in supporting the efectiveness of intemal control on sales. The results show that PT Indomilk already applies a proper system to ensure an efective intemal control on sales. This is evident from a computerized accounting system and the Division of duties already used by the company. All employees to be able to run properly in accordance with their functions. With an increasingly efective safeguards, the vision and mission of the company can be reached and the company can continue operations running smoothly. Keywords: accounting information systems sales, the efectiveness of internal control, internal control of sales